The framework for athletes to win in and outside of the classrooms - the figure of the student-athletes and the skills acquired in dual careers - Canhoto, Francisco Manuel Pontes Dias (2022)
This work aims to study the challenges that high-performing athletes face when conciliating their sports activities with a second occupation and the skills developed during that time. Having best practices from other countries as benchmarks, we contrast them with the experience of Portuguese athletes, in particular, concerning the ability to conciliate their sports activities with their academic careers. We find that there are considerable improvements at the financial, infrastructure, and regulatory levels to close the gap with our benchmark cases.